First record of Prostemmatinae (Heteroptera: Nabidae) from Chile - Faundez, Eduardo (My University, 2024)
The damsel bug subfamily Prostemmatinae is recorded for the first time from Chile, with the species Pagasa (Lampropagasa) fuscipennis Reuter, 1909. Specimens were obtained from Nuble and Araucanía Regions.
Primer registro de Prostemmatinae (Heteroptera: Nabidae) en Chile
Keywords: cimicomorpha; faunistics; hemiptera; new record